PENYELESAIAN SENGKETA ATAS PEMBERIAN KETERANGAN TIDAK BENAR DEBITOR DALAM PROSES KEPAILITAN - Hlaaillah Diah Permada Margadineta, Qifatah; Nugroho, Lucky Dafira (ADHAPER: Jurnal Hukum Acara Perdata, 2023)
Abstract The bankruptcy process and the cooperative attitude of the bankrupt debtor are important factors for the successful resolution of cases. Law Number 37 of 2004 concerning Bankruptcy and PKPU (UUK-PKPU) is based on the principles of balance and fairness, one of which is to minimize debtor fraud. However, in practice, there are still cases of fraud that are not explicitly regulated, such as the provision of false statements regarding the debtor's assets. This study examines two issues, namely the impact of false statements by debtors on bankruptcy assets and the legal liability of debtors who cause harm to third parties. The research method used is normative with a legislative approach, conceptual approach, and comparative approach, referring to the Malaysian Insolvency Act 1967. The issues are analyzed through Decision Number 06/Pdt.Sus-Plw. Pailit/2018/PN Niaga Surabaya, which shows a legal vacuum in the UUK-PKPU because it does not require the accuracy of debtor information. As a result, false statements do not affect bankruptcy assets according to Article 26 paragraph (2), so that the debtor's liability can be settled through the UUK-PKPU or Article 1365 of the Civil Code. Keywords: Liability; Debtor; Bankruptcy; Third Party; Loss   Abstrak Proses kepailitan, sikap kooperatif debitor pailit merupakan faktor penting bagi keberhasilan penyelesaian perkara. Undang-Undang Nomor 37 Tahun 2004 tentang Kepailitan dan PKPU (UUK-PKPU) berlandaskan prinsip keseimbangan dan keadilan, salah satunya untuk meminimalkan kecurangan debitor. Namun, dalam praktik masih ditemukan tindakan penipuan yang belum diatur secara tegas, seperti pemberian pernyataan palsu mengenai harta debitor. Penelitian ini mengkaji dua permasalahan, yaitu dampak pernyataan palsu debitor terhadap harta pailit serta tanggung jawab hukum debitor yang merugikan pihak ketiga. Metode penelitian Normatif dengan pendekatan perundang-undangan, pendekatan konseptual dan pendekatan komparatif. merujuk Malaysia Insolvency Act 1967 Permasalahan dianalisis melalui Putusan Nomor 06/Pdt.Sus-Plw.Pailit/2018/PN Niaga Surabaya yang menunjukkan adanya kekosongan hukum dalam UUK-PKPU karena tidak mewajibkan kebenaran informasi debitor. Akibatnya, pernyataan palsu tidak berdampak pada harta pailit menurut Pasal 26 ayat (2) sehingga Tanggung jawab debitor dapat diselesaikan melalui UUK-PKPU atau Pasal 1365 BW. Kata Kunci: Tanggung Gugat; Debitor; Pailit; Pihak Ketiga; Kerugian